BIRT : a field guide to reporting - Peh, Diana (Eclipse series., 2008)
The world-wide developer community has downloaded over three million copies of BIRT (Business Intelligence and Reporting Tools) from the Eclipse web site. Built on the open-source Eclipse platform, BIRT is a powerful reporting system that provides an end-to-end solution, from creating and deploying reports to integrating report capabilities in enterprise applications. The first in a two-book series about this exciting technology, BIRT, Second Edition: A Field Guide to Reporting is the authoritative guide to using BIRT Report Designer, the graphical tool that enables users of all levels to build reports, simple to sophisticated, without any programming. BIRT, Second Edition: A Field Guide to Reporting is an essential resource for users who want to create presentation quality reports from day one. The extensive examples, step-by-step instructions, and abundant illustrations help new users develop their report design skills quickly. Power users can find the information they need to make the most of the product's rich set of features to build complex and compelling reports. By the time you finish this book, you learn the following and more Design effective business and corporate reports that convey information through images, charts, tables, and cross tabs Build reports using data from a variety of sources, including databases, XML documents, spreadsheets, and web services Enliven reports with interactive features, such as hyperlinks, Tooltips, and highlighting Create consistently styled reports and collaborate with other report designers through the use of templates and libraries of reusable elements Localize reports for an international audience This second edition, revised and expanded, adds updated examples and covers all the new and improved product features, including Cross tabs and OLAP cubes New chart types, including Gantt, bubble, tube, and cone charts Web services as a new data source New report output formats, including doc, ppt, xls, and PostScript The capability for reports to reference CSS Localization of report parameter and data values.